Analysis of the safety and efficacy of different plasma concentrations of pirfenidone in patients with idiopathic pulmonary fibrosis - Li, Hui; Yang, Jing; Chen, Shanshan; Wang, Peile; Yu, Xueqing; Zhou, Qingwei; Zhang, Xiaojian; Zhang, Guojun (Frontiers in Pharmacology, 2022)
The high incidence and mortality of idiopathic pulmonary fibrosis (IPF) have led to the widespread use of antifibrotic drugs such as pirfenidone; however, the associated adverse reactions greatly vary among individuals and the dose is not fixed. To date, no reliable blood concentration range of pirfenidone is available to monitor adverse reactions and clinical efficacy. This real study assessed the efficacy and safety of different plasma concentrations of pirfenidone in patients with IPF. The study included 99 patients with IPF orally treated with pirfenidone capsules for at least 52 weeks. Ultra-performance liquid chromatography–mass spectrometry was used to analyze drug plasma concentrations. The annual rate of forced vital capacity (FVC) decline, assessed at week 52, was set as the primary end point. Secondary end points were the change from the baseline in the 6-minute walk distance (6MWD) and the time to the first acute exacerbation of IPF, both of which evaluated over 52 weeks. In the total population, the annual FVC decline in the high-concentration group was -90.0 mL per year versus -260.0 mL per year in the low-concentration group, for a between-group difference of 190.3 mL per year. The proportion of patients treated with high plasma concentrations of pirfenidone who showed an absolute decline of ≥ 10% in FVC% predicted, with a 6MWD reduction of ≥ 50 m, or died, was lower than that of patients treated with low plasma concentrations of pirfenidone. High concentrations of pirfenidone reduced the risk of acute exacerbation in patients with IPF. Considerable differences were not observed for the total St. George’s Respiratory Questionnaire score or the rates of death between the high- and low-concentration groups. Mild to moderate adverse events, mainly involving the gastrointestinal system and the skin, were more common in the high-concentration group than in the low-concentration group but did not lead to termination of treatment in most cases. Our results suggest that treatment of IPF with high blood concentration of pirfenidone is both safe and effective. In the case of tolerable adverse reactions, patients with IPF may benefit from high concentrations of pirfenidone.